EVALUATION OF ANTICANCER ACTIVITY OF PARKINSONIA ACULEATA LEAVES EXTRACT ON EHRLICH'S ASCITES CARCINOMA-INDUCED MICE. - A, Prameela Rani; E, NAGARJUNA BABU; S, Prem Madhur; Reddy D, Ravi Chandra Sekhara; Kumar K, Phani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of the study was to investigate the anticancer activity of the ethanolic extract of Parkinsonia aculeata (EEPA) leaves. Methods: Anticancer activity of P. aculeata (EEPA) of leaf extract was evaluated in Swiss albino mice against Ehrlich ascites carcinoma (EAC) cell line at the doses of 200 and 400 mg/kg body weight orally. The extracts were administered for 14 consecutive days. 24 h of the last dose and 18 h of fasting, the mice were sacrificed, and the anticancer effect of EEPA was assessed by evaluating tumor volume, viable and nonviable tumor cell count, tumor weight, hematological parameters, and biochemical parameters of EAC bearing mice. Results: P. aculeata extracts showed a significant decrease in (p<0.01) tumor volume, viable cell count, tumor weight, and elevated the life span of EAC bearing mice. Hematological profile such as red blood cell, hemoglobin count reverted to normal level in EEPA treated mice. The extracts significantly (p<0.05) decreased the levels of lipid peroxidation and significantly (p<0.05) increased the levels of reduced glutathione, superoxide dismutase and catalase. Conclusion: The results showed that the EEPA was effective in inhibiting the tumor growth in ascitic models and that is comparable to 5-fluorouracil. Â 